1983
DOI: 10.1577/1548-8659(1983)112<705:atoatf>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity of Ammonia to Fathead Minnows

Abstract: The acute toxicity of ammonia to fathead minnows Pimephales promelas was measured in 35, 96‐hour, flow‐through tests. The fish were from both wild and hatchery‐reared stocks, and ranged in size from 0.1 to 2.3 g. The 96‐hour median lethal concentrations (LC50) ranged from 0.75 to 3.4 mg/liter un‐ionized ammonia (34 to 108 mg/liter total ammonia‐nitrogen). The toxicity of ammonia decreased as temperature increased over the range 12 to 22 C. There was no significant relationship between ammonia toxicity and diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

1986
1986
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 7 publications
2
22
0
1
Order By: Relevance
“…Ammonia toxicity to the prawn was doubled when dissolved oxygen decreased from 55 to 27% saturation (Wajsbrot et al 1990). Thurston et al (1983), however, found no correlation between oxygen level and ammonia toxicity to fathead minnows Pimephales promelas. Hiroki (1978) demonstrated that hypoxic tolerance in 3 species of marine gastropods (Littorina ziczac, Neritina vorginea and Olivella verreuxii) decreased in the presence of H 2 S. Similarly, Kang et al (1993) showed that H 2 S decreased the hypoxic tolerance of the crab Portunus trituberculatus.…”
Section: Interactions Among Factorsmentioning
confidence: 94%
“…Ammonia toxicity to the prawn was doubled when dissolved oxygen decreased from 55 to 27% saturation (Wajsbrot et al 1990). Thurston et al (1983), however, found no correlation between oxygen level and ammonia toxicity to fathead minnows Pimephales promelas. Hiroki (1978) demonstrated that hypoxic tolerance in 3 species of marine gastropods (Littorina ziczac, Neritina vorginea and Olivella verreuxii) decreased in the presence of H 2 S. Similarly, Kang et al (1993) showed that H 2 S decreased the hypoxic tolerance of the crab Portunus trituberculatus.…”
Section: Interactions Among Factorsmentioning
confidence: 94%
“…(1983) suggest that a reduction in the level of dissolved oxygen in the water increases the toxicity of ammonia to fish. Less clear cut results were obtained, however, for rainbow trout ( O. mykiss )(Thurston & Russo, 1983) and fathead minnows ( Pimephales promlas Rafinesque)(Thurston et al ., 1983). Respiration by the fish will reduce dissolved oxygen and increase carbon dioxide levels which will decrease the pH value of the water.…”
Section: Osmoregulation and Respirationmentioning
confidence: 99%
“…In the 96-h LC50 test for grass carp the highest total ammonia nitrogen measured was 0.6 mg/L and the UI never exceeded 0.08 mg/L in any container. We could not find ammonia toxicity values for golden shiners and grass carp but the UI 96-h LC50 values for four other cyprinids-bighead carp Hypophthalmichthys nobilis, silver carp H. molitrix, common carp Cyprinus carpio, and fathead minnow-were 0.30, 0.38, 0.66, and 1.0-2.5 mg/L, respectively (Thurston et al 1983;Zu et al 1994). The grass carp in our studies were subjected to UI levels that were much lower than the LC50 values reported for the other cyprinids, and the time during which they were exposed to the levels recorded at the end of our treatment period would certainly be much less than 96 h. Obiekezie and Okafor (1995) found that the 24-h LC50 estimate for African sharptooth catfish exposed to praziquantel was 13.4 mg/L; this indicates that praziquantel is about four times more toxic to this clariid than to the cyprinids tested in our study.…”
Section: Resultsmentioning
confidence: 81%